2017
DOI: 10.1038/srep40555
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics reveals dramatic lipid compositional changes in the maturing postnatal lung

Abstract: Lung immaturity is a major cause of morbidity and mortality in premature infants. Understanding the molecular mechanisms driving normal lung development could provide insights on how to ameliorate disrupted development. While transcriptomic and proteomic analyses of normal lung development have been previously reported, characterization of changes in the lipidome is lacking. Lipids play significant roles in the lung, such as dipalmitoylphosphatidylcholine in pulmonary surfactant; however, many of the roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 67 publications
4
70
1
Order By: Relevance
“…Detailed lipidomics characterization of adult mouse lung tissue revealed elevated levels of long chain polyunsaturated fatty acids and LPC species in adult mice in comparison with pups. [34] This observation was attributed to a greater state of inflamation of adult lungs maintained in a healthy state through a fine balance between pro-inflamatory and pro-resolution lipids and associated protein mediators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed lipidomics characterization of adult mouse lung tissue revealed elevated levels of long chain polyunsaturated fatty acids and LPC species in adult mice in comparison with pups. [34] This observation was attributed to a greater state of inflamation of adult lungs maintained in a healthy state through a fine balance between pro-inflamatory and pro-resolution lipids and associated protein mediators.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent lipidomics study, these PC species have been also observed as abundant components of lung tissue. [34]…”
Section: Resultsmentioning
confidence: 99%
“…The data were normalized using global median centering, in which each sample was scaled by the median of its observed abundance values. This approach has been described previously 104107 and utilized in a number of other studies 108110 . Lipids were evaluated using analysis of variance (ANOVA) with a Dunnett test correction to compare infected to mock at each timepoint (24 hours and 48 hpi).…”
Section: Methodsmentioning
confidence: 99%
“…Lipidomic analysis was performed on BALF at PNNL as previously described (52). Proteomics analysis was performed on BALF at Pacific Northwest Laboratory using a label-free approach (53) as detailed in Supplemental Methods.…”
Section: Methodsmentioning
confidence: 99%